Phenolic composition, antioxidant activity and health benefits of Tartary (Fagopyrum tataricum Gaerth) and common (F. esculentum Moench) buckwheat grains: A review - Balwinder Singh; Somna Oberoi; Amritpal Kaur (Food Chemistry Advances)
Buckwheat (BW) grains are excellent suppliers of polyphenols with important health promoting qualities. The phenolic acids (protocatechuic, p-hydroxybenzoic, gallic, p-coumaric, chlorogenic, syringic, ferulic, vanillic and caffeic acids), flavonoids (rutin, quercetin, kaempferol, vitexin) and anthocyanins have been identified as phenolic compounds from common BW (CBW) and Tartary BW (TBW) grains. The outer hull and bran section of BW contains majority of these compounds. The amount of flavonoids (rutin and quercetin) and antioxidant activity were higher for all fractions of TBW than the CBW grains. This review consolidates and critically evaluates the current knowledge on the phenolic composition in BW grains, effect of different processing methods on phenolic composition and discussion of antioxidant activity and therapeutic benefits of BW grains. By comparing CBW and TBW, the review provides valuable insights into how their distinct phenolic profiles contribute to their bioactivities, such as anti-inflammatory, anti-diabetic, anti-cancer, and cardiovascular protective effects. Furthermore, the review highlights the impact of various processing methods on these bioactive compounds, thus offers guidance to food processing industries in optimizing the nutritional and therapeutic value of BW-based products. This review is essential for food scientists, nutritionists, and health professionals aiming to develop and promote BW-enriched functional foods.